A formação de professoras para o ensino de ciências nas séries iniciais: análise dos efeitos de uma proposta inovadora - Augusto, Thaís Gimenez Da Silva [UNESP]; Amaral, Ivan Amorosino Do (Programa de Pós-Graduação em Educação para a Ciência, Universidade Estadual Paulista (Unesp), Faculdade de Ciências, campus de Bauru., 2015)
This work is based on empirical research data and aims at analyzing the effectiveness of an innovative approach applied during the training of multipurpose teachers who teach sciences in primary schools. The researched teachers were studying Pedagogy at Unicamp due to an agreement among the university and city halls belonging to the metropolitan area of Campinas. The declared practices and ideas carried out by 13 teachers who teach sciences were researched. Previous data and information given during and at the end of the course through questionnaires, essays, observations and interviews was used. Although the majority of teachers seemed to have understood the key ideas of the course and promoted changes in their classes, it was concluded that the lack of previous knowledge, concerning specific science content, and the small number of hours available for teaching were the main factors which make it impossible for a wider apprehension of some ideas highlighted in the course to be present.

Pesquisa empírica que tem como objetivo analisar os efeitos de uma proposta inovadora de formação em serviço nas concepções e práticas declaradas de professoras polivalentes que lecionam Ciências nas séries iniciais. As professoras pesquisadas cursavam Licenciatura Plena em Pedagogia na Unicamp, por um convênio entre a universidade e as prefeituras municipais da Região Metropolitana de Campinas. Pesquisou-se quais as concepções e práticas declaradas, de 13 professoras, sobre o ensino de Ciências para as séries iniciais anteriormente, durante o transcorrer e ao final da disciplina, por meio de: questionários, redações, observação do curso e entrevistas. Concluiu-se que, embora a maioria das professoras pareça ter compreendido as ideias-chave da disciplina e tenha promovido mudanças em suas práticas docentes, a falta de conhecimento prévio de conteúdos específicos de Ciências e a pequena carga horária disponível foram os principais fatores que impossibilitaram a apreensão mais abrangente de algumas das ideias enfocadas pela disciplina.
Training teachers to teach sciences in elementary school: an analysis concerning the effectiveness of an innovative approach
Keywords: Science teaching; Teachers training; Teaching practice; Elementary school; Ensino de ciências; Formação de professores; Séries iniciais; Prática docente; Ensino Fundamental